A Systematic Analysis of Inclusion Teachers' Work Engagement: An In-Depth Study of Inclusion Teachers' Dedication, Passion, and Teachers’ Appreciation of Inclusion - Muchamad Irvan; Anggita Hemaylia Putri; Ranti Novianti (Institut of Shanti Bhuana, 2024)
Work engagement of inclusion teachers is a crucial factor affecting the quality of education for children with special needs in regular school settings. The role of the inclusion teacher is not only limited to the delivery of learning materials, but also includes dedication, passion, and appreciation for the special needs of these children. The method used is a Systematic Literature Review (SLR) which allows for a detailed examination of structured data search steps in the context of aspects of work engagement in inclusive teachers. Searches were conducted through databases such as Google Scholar, Semantic Scholar, Mendeley, and ResearchGate. The literature reviewed is limited to the years 2012-2022. Literature search keywords include Teachers' Work Engagement, Inclusive Teachers, and Inclusive Teachers' Vigor, Dedication, and Absorption. The results show that the dedication of inclusive teachers plays a key role in creating a learning environment that supports the development of children with special needs. Passion and appreciation of responsibility also contribute to determining the quality of education provided. Inclusive teachers with high levels of work engagement are considered important change agents in improving the quality of education for children with special needs.